2001
DOI: 10.1016/s0014-5793(01)03116-7
|View full text |Cite
|
Sign up to set email alerts
|

A lipid transfer protein binds to a receptor involved in the control of plant defence responses

Abstract: Lipid transfer proteins (LTPs) and elicitins are both able to load and transfer lipidic molecules and share some structural and functional properties. While elicitins are known as elicitors of plant defence mechanisms, the biological function of LTP is still an enigma. We show that a wheat LTP1 binds with high affinity sites. Binding and in vivo competition experiments point out that these binding sites are common to LTP1 and elicitins and confirm that they are the biological receptors of elicitins. A mathemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
102
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(107 citation statements)
references
References 32 publications
(47 reference statements)
4
102
0
1
Order By: Relevance
“…The use of LTP, a cryptogein antagonist that binds to the same high-affinity site at the plasma membrane, but triggers neither signaling events (Buhot et al, 2001) nor endocytosis (this study), emphasizes the role of signaling by cryptogein as the release mechanism for endocytosis. Interestingly, the transient wave of CCPs observed in the first 10 min after cryptogein addition exhibits the same kinetics as the typical transient production of ROS (Simon-Plas et al, 1997).…”
Section: Ros Production Is Correlated With Endocytosismentioning
confidence: 83%
See 1 more Smart Citation
“…The use of LTP, a cryptogein antagonist that binds to the same high-affinity site at the plasma membrane, but triggers neither signaling events (Buhot et al, 2001) nor endocytosis (this study), emphasizes the role of signaling by cryptogein as the release mechanism for endocytosis. Interestingly, the transient wave of CCPs observed in the first 10 min after cryptogein addition exhibits the same kinetics as the typical transient production of ROS (Simon-Plas et al, 1997).…”
Section: Ros Production Is Correlated With Endocytosismentioning
confidence: 83%
“…In tobacco cells, both cryptogein and an LTP1 from wheat (Triticum aestivum) bind to an identical high-affinity specific site located on the plasma membrane (Buhot et al, 2001). In addition, in vivo competition experiments have indicated that the binding sites for both proteins are their true biological receptor because addition of increasing concentrations of LTP1 reduced signaling events induced by cryptogein (Buhot et al, 2001). Nevertheless, LTP alone did not trigger any of the classical responses induced by cryptogein in tobacco cells, such as extracellular alkalinization or oxidative burst.…”
Section: Endocytosis Requires Not Only Binding To the Receptor But Amentioning
confidence: 99%
“…Thirdly, a kinetic analysis of the elicitin binding curves, using the allosteric model of Monod [58], confirms that these receptors could be represented by an allosteric model corresponding to an oligomeric structure with four identical subunits [59]. Taking these results into account, we proposed that the elicitin receptor could be a ligand-dependent calcium channel constituted of a quadrimeric complex as shown in Figure 3, which summarizes the initial molecular events involving activation of elicitin by sterol loading that drive the elicitor function [56,59].Finally, all the elicitins tested are able to bind to the same sites (with a similar affinity), suggesting that they are recognized by the same receptors, although they induce differential cell and plant responses [40]. These apparently contradictory observations remained to be explained.…”
mentioning
confidence: 64%
“…Finally, the effects of LTP1 on tobacco cells were analyzed. The addition of increasing concentrations of LTP1 reduced the production of active oxygen species, induced by a fixed cryptogein concentration [59]. This result indicates that the binding sites of LTP1 and cryptogein are their true biological receptors.…”
mentioning
confidence: 74%
See 1 more Smart Citation